78 A Lockdown Dilemma; Ingestion of Magnetic Beads Presenting as Right Iliac Fossa Pain and Sub-Acute Small Bowel Obstruction. (4th May 2021) - Oyewole, B; Sandhya, A; Maheswaran, I; Campbell-Smith, T
Abstract: A 13-year-old girl presented with a three-day history of migratory right iliac fossa pain. Observations and inflammatory markers were normal, and an ultrasound scan was inconclusive. A provisional diagnosis of non-specific abdominal pain or early appendicitis was made, and she was discharged with safety netting advice. She represented six days later with ongoing abdominal pain now associated with multiple episodes of vomiting; hence, the decision was made to proceed to diagnostic laparoscopy rather than a magnetic resonance scan for further assessment as recommended by the radiology department. Intra-operative findings revealed 200mls of serous fluid in the pelvis, normal-looking appendix, dilated stomach, and a tangle of small bowel loops. Blunt and careful dissection revealed fistulous tracts that magnetized the laparoscopic instruments. A mini-laparotomy was performed with the extraction of fourteen magnetic beads and the repair of nine enterotomies. Foreign body ingestion is a known cause of abdominal pain, which in some cases might mimic or even be the cause of acute appendicitis. This case highlights the importance of careful history taking in children presenting with acute abdominal pain of doubtful aetiology.